Inflammatory and metalloproteinases profiles predict three-month poor outcomes in ischemic stroke treated with thrombolysis. Issue 9 (September 2017) - Gori, Anna Maria; Giusti, Betti; Piccardi, Benedetta; Nencini, Patrizia; Palumbo, Vanessa; Nesi, Mascia; Nucera, Antonia; Pracucci, Giovanni; Tonelli, Paolina; Innocenti, Eleonora; Sereni, Alice; Sticchi, Elena; et al.
Inflammatory mediators and metalloproteinases are altered in acute ischemic stroke (AIS) and play a detrimental effect on clinical severity and hemorrhagic transformation of the ischemic brain lesion. Using data from the Italian multicenter observational MAGIC (MArker bioloGici nell'Ictus Cerebrale) Study, we evaluated the effect of inflammatory and metalloproteinases profiles on three-month functional outcome, hemorrhagic transformation and mortality in 327 patients with AIS treated with intravenous thrombolys in according to SITS-MOST (Safe Implementation of Thrombolysis in Stroke-MOnitoring STudy) criteria. Circulating biomarkers were assessed at baseline and 24 h after thrombolysis. Adjusting for age, sex, baseline glycemia and National Institute of Health Stroke Scale, history of atrial fibrillation or congestive heart failure, and of inflammatory diseases or infections, baseline alpha-2macroglobulin (A2M), baseline serum amyloid protein (SAP) and pre-post tissue-plasminogen activator (tPA) variations (Δ) of metalloproteinase 9, remained significantly and independently associated with three-month death [OR (95% CI):A2M:2.99 (1.19–7.53); SAP:5.46 (1.64–18.74); Δmetalloproteinase 9:1.60 (1.12–2.27)]. The addition of baseline A2M and Δmetalloproteinase 9 or baseline SAP and Δmetalloproteinase 9 (model-2 or model-3) to clinical variables (model-1) significantly improved the area under curve for prediction of death [model-2 with A2M: p = 0.0205; model-3 with SAP: p = 0.001]. In conclusion, among AIS patients treated with thrombolysis, circulating A2M, SAP and Δmetalloproteinase 9 are independent markers of poor outcome. These results may prompt controlled clinical research about agents antagonizing their effect.